Hotspots and frontiers of extracellular vesicles and lung cancer: a bibliometric and visualization analysis from 2002 to 2024 - Zelin Yang; Jie Tian (Discover Oncology)
Abstract Purpose Extracellular vesicles (EVs) play a crucial role in promoting tumor progression in lung cancer (LC) and serve as potential diagnostic and therapeutic targets. Despite their significance, no comprehensive bibliometric analysis of global research on EVs and LC has been conducted. This analysis aims to address this gap by highlighting key trends, contributors, and future directions. Methods A total of 1,002 publications from 2002 to 2024 were extracted from the Web of Science Core Collection. The analysis was conducted using VOSviewer, CiteSpace, and the R package “Bibliometrix”. Results The study includes contributions from 6337 researchers across 1339 institutions in 60 countries, with findings published in 404 journals. The number of publications has steadily increased, with China and the United States leading the output, and Nanjing Medical University being the largest contributor. Cancer published the most articles, while Cancer Research had the highest number of co-citations. Jing Li was the most productive author, and C. Thamesry was the most frequently co-cited. Major research themes included “the pro-metastatic role of exosomal miRNAs”, “liquid biopsy diagnostics”, “aptamer-binding proteomics diagnosis”, “macrophage regulation by autophagy and hypoxia”, “anti-cancer effects of exosomes”, “nanomedicine delivery and immunotherapy”, “non-coding RNA markers”, and “immune regulation of the tumor microenvironment”. Future studies are expected to focus on “emerging diagnostic biomarkers”, “tumor microenvironment regulation”, and “nanomedicine delivery”. Conclusion This is the first bibliometric analysis on EVs and LC, providing an overview of global research trends and emerging therapeutic strategies. The findings provide valuable insights for future investigations and treatment optimization.